Research of the Flow Attenuation Mechanism of a Double-Suction Pump - Meng, Dongrong; Jiang, Ting; Liu, Zhengguang; Zhao, Meng; Jiang, Wei; Hou, Gaoyang (Frontiers in Energy Research, 2022)
As an important machine for energy conversion and fluid transmission, centrifugal pump has the advantages of high efficiency, reliable performance and easy adjustment. In order to improve the stability of the pump, this paper adopts the method of experiment and numerical simulation in the pump, and studies the variation of the vibration characteristics in the operation process. Based on the numerical simulation results, the intake condition and the cavitation inside the centrifugal pump are analyzed and summarized, which reveals the flow attenuation mechanism of a Pumping Station. The main results of the work reported in this paper are as follows: (1) Various experimental schemes to monitor the vibration of centrifugal pumps in real time have been designed. The vibration characteristics of the pumps have been significantly improved by adding special trash barriers. (2) The gas entering the pump was not enough to affect the normal operation of the pump, but cavitation did occur in the actual operation process. (3) The critical net positive suction head under three conditions is calculated to be 8.9m, 10.9m and 12.9m, respectively.